Um novo esquema de proteção para redes PON TDM - Carvalho, Maurício Moderno de (2008)
By adopting a ring topology and optical switches we propose a novel protection mechanism for time division multiplexed passive optical network (TDM-PON) that provides resilience against multiple network fails. Some protection schemes have been proposed in order to give resilience for passive optical network (PON) as defined at ITU-T Recommendation G983.1. However that recommendation defines the optical distribution network (ODN) and equipment duplication to protect it against multiple points of fail. We propose a ring topology with dual fibers paths capable to protect the network by switching these lines individually according to the local alarms detected by each optical network unit (ONU). According to our proposal neither equipment nor network should be duplicated to provide survivability to the system.